2010
DOI: 10.1186/1472-6920-10-41
|View full text |Cite
|
Sign up to set email alerts
|

Visiting medical student elective and clerkship programs: a survey of US and Puerto Rico allopathic medical schools

Abstract: BackgroundNo published reports of studies have provided aggregate data on visiting medical student (VMS) programs at allopathic medical schools.MethodsDuring 2006, a paper survey was mailed to all 129 allopathic medical schools in the United States and Puerto Rico using a list obtained from the Association of American Medical Colleges. Contents of the survey items were based on existing literature and expert opinion and addressed various topics related to VMS programs, including organizational aspects, program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
1
10
0
2
Order By: Relevance
“…This discrepancy may be attributable to changing attitudes among applicants and programs over time and the recent advent of a centralized, online application service for VSEs (Visiting Student Application Service). In line with our findings, recent studies reveal that both applicants and program directors view VSEs as a chance to increase applicants' chances of matching at host institutions [2,3,8]. Further investigation is needed to determine the underlying cause of this trend; however, a perceived lack of trustworthiness between applicants and program directors may play a role.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This discrepancy may be attributable to changing attitudes among applicants and programs over time and the recent advent of a centralized, online application service for VSEs (Visiting Student Application Service). In line with our findings, recent studies reveal that both applicants and program directors view VSEs as a chance to increase applicants' chances of matching at host institutions [2,3,8]. Further investigation is needed to determine the underlying cause of this trend; however, a perceived lack of trustworthiness between applicants and program directors may play a role.…”
Section: Discussionsupporting
confidence: 89%
“…Applicants view these electives as opportunities to increase the likelihood of matching at desired programs, an attitude reciprocated by program directors [2,3]. However, past work has called the value of VSEs into question based on an apparent lack of efficacy.…”
Section: Introductionmentioning
confidence: 98%
“…One such opportunity opened to students is the freedom to visit other medical schools, outside of the students’ home institution, often in conjunction with application to residency programs [3]. We have observed informally that visiting rotations have become increasingly popular.…”
Section: Introductionmentioning
confidence: 99%
“…Although many senior physicians and faculty members believe that the programs are of uncertain academic value and have proposed cutting down on the clinical electives and investing the time regained in structured academic activities (6, 7) a recent survey revealed that the most common reason (90%) for medical schools to incorporate visiting elective programs was "recruitment for residency programs" (4). In a reciprocating factor students ranked "desire to do a residency at the institution" as the primary reason for doing an elective at a certain institution (4).…”
mentioning
confidence: 98%